Self-Medication in University Students in Brazil: A literature review (Research, Society and Development, 2023)
Self-medication is the use of medication without qualified professional guidance. It is a public health problem that especially affects the student population, who often turn to medication to improve academic performance or treat common illnesses. This study aimed to analyze the risk of self-medication and adverse reactions in the Brazilian university population. This is an integrative literature review using the Scielo, BVS and CAPES Portal databases. The descriptors used were: Self-medication; Students; Adverse effects. The AND operator was used to refine the search. The following inclusion criteria were defined: complete articles, dissertations and theses freely available; publication language in Portuguese. Articles that did not meet the inclusion criteria, duplicated articles or those that deviated from the theme were excluded. 275 studies were found. After applying the inclusion and exclusion criteria, 22 studies were selected. Self-medication is a public health problem and it is a reality especially among university students, especially in courses in the health area. Analgesics/antipyretics, antispasmodics, antacids and antidiarrheals, as well as antibiotics, vitamins and contraceptives are the drugs most used by the student population. Publicity and advertising of medicines, availability and access to medicines, lack of access to health services and delay in care have substantial impacts on the increase in the practice of self-medication.